Discourse on Amar Ma’ruf Nahi Munkar in Islamic Theology - Akhmad Jazuli Afandi (Fakultas Agama Islam, Universitas Hasyim Asy'ari, 2024)
Abstract: This article aims to provide an in-depth analysis of the theory and application of Amar Ma'ruf Nahi Munkar in Islamic Theology. Amar ma'ruf nahi munkar is the practical side of Shari’a Islamiyah; regardless of their theological affiliation, every Muslim must perform it. This research thoroughly examines the primary issue through descriptive methodology and hermeneutic analysis to accomplish this objective. In Turâth Islamy, the ulama understands it differently, as the data collection and analysis results show. Qâdi 'Abd al-Jabbâr, one of the Mu'tazilite scholars, wrote in Sharh al-Ushûl al-Khamsah discussing the concept of Amar Makruf Nahi Munkar; al-Ghazali and al-Zamakhsarî have also reflected on it. The most authoritative sources in the Muslim world show that the Amar Makruf Nahi Munkar contained the element and value of humanism. It provides various important points and guidelines that individuals can apply in real-life situations. Among these points and guidelines are the doctrine that judging for good must be done in stages, according to the competence of the offender, and using appropriate methods.